Software for calibrating a digital image processing - Lang, Kathrin (2014)
This work is about learning tool wich provides the necessary parameters for a program controlling robots of type LUKAS at the Faculty of Mechanical Engineering. The robot controlling program needs various parameters depending on its environment, like the light intensity distribution, and camera settings as exposure time and gain raw. These values have to be transmitted from the learning tool to the robot controlling software. Chapter one introduces the robots of type LUKAS which are created for the RoboCup Small Size League. Furthermore, it introduces the camera used for image processing. The second chapter explains the learning process according to Christoph UBfeller and deduces the requirements for this work. In the third chapter theoretical basics concerning image processing, wich are fundamental for this work, are explained. Chapter 4 describes the developed learning tool which is used for the learning process and generates the required parameters for the robot controlling software. In chapter five practical test with two persons are represented. The sixth and last chapter summarizes the results.